Identification and Validation of Potential Biomarkers and Pathways for Idiopathic Pulmonary Fibrosis by Comprehensive Bioinformatics Analysis. (5th July 2021) - Qian, Weibin; Cai, Xinrui; Qian, Qiuhai; Zhang, Xinying
Abstract : Objective . Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive, irreversible, high-mortality lung disease, but its pathogenesis is still unclear. Our purpose was to explore potential genes and molecular mechanisms underlying IPF. Methods . IPF-related data were obtained from the GSE99621 dataset. Differentially expressed genes (DEGs) were identified between IPF and controls. Their biological functions were analyzed. The relationships between DEGs and microRNAs (miRNAs) were predicted. DEGs and pathways were validated in a microarray dataset. A protein-protein interaction (PPI) network was constructed based on these common DEGs. Western blot was used to validate hub genes in IPF cell models by western blot. Results . DEGs were identified for IPF than controls in the RNA-seq dataset. Functional enrichment analysis showed that these DEGs were mainly enriched in immune and inflammatory response, chemokine-mediated signaling pathway, cell adhesion, and other biological processes. In the miRNA-target network based on RNA-seq dataset, we found several miRNA targets among all DEGs, like RAB11FIP1, TGFBR3, and SPP1. We identified 304 upregulated genes and 282 downregulated genes in IPF compared to controls both in the microarray and RNA-seq datasets. These common DEGs were mainly involved in cell adhesion, extracellular matrix organization, oxidation-reduction process, and lung vasculature development. In the PPI network, 3 upregulated and 4 downregulated genes could be considered hub genes, which were confirmed in the IPF cell models. Conclusion . Our study identified several IPF-related DEGs that could become potential biomarkers for IPF. Large-scale multicentric studies are eagerly needed to confirm the utility of these biomarkers.